2013
DOI: 10.31910/rudca.v16.n1.2013.859
|View full text |Cite
|
Sign up to set email alerts
|

Influencia de la sombra y de las micorrizas sobre el crecimiento de plantas de lulo (Solanum quitoense Lam.)

Abstract: Palabras clave: Sombreado, área foliar, peso específico de las hojas, materia seca.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
1
4
0
1
Order By: Relevance
“…The rhizosphere microbiota is known to extend the adaptive capacity of plants (i.e., phenotypic plasticity) to environmental stresses (Venturi & Keel, ). The overall beneficial effect of the interaction between micro‐organisms and plant growth, under contrasting light environments, has also been reported in studies with mycorrhizal growth promoters (Aguilar‐Chama & Guevara, ; Casierra‐Posada, Peña‐Olmos, Peñaloza, & Roveda, ; Konvalinková & Jansa, ).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The rhizosphere microbiota is known to extend the adaptive capacity of plants (i.e., phenotypic plasticity) to environmental stresses (Venturi & Keel, ). The overall beneficial effect of the interaction between micro‐organisms and plant growth, under contrasting light environments, has also been reported in studies with mycorrhizal growth promoters (Aguilar‐Chama & Guevara, ; Casierra‐Posada, Peña‐Olmos, Peñaloza, & Roveda, ; Konvalinková & Jansa, ).…”
Section: Discussionsupporting
confidence: 53%
“…For instance, in rice, from which the rhizobacteria used in this study were originally isolated, growth is higher with B. pyrrocinia inoculation than with P. fluorescens inoculation (Nascente et al., ; Rêgo et al., ), or with co‐inoculation with these rhizobacteria (Rêgo et al., ). The synergistic effect of B. pyrrocinia and P. fluorescens , promoting growth in B. brizantha , was possibly a response of increased nutrient flow (Casierra‐Posada et al., ; Paredes & Lebeis, ), phytohormone production, such as auxin or cytokinin, or decreased plant ethylene levels, through the action of the enzyme ACC deaminase (Ahemad & Kibret, ; Vimal et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…and fertilization using 15-15-15 (N-P-K of 200 g plant −1 ). AMF increased the landfill capacity of the root system, thereby increasing the photosynthetic rate and growth of the plant [52].…”
Section: Plant Height and Stem Diametermentioning
confidence: 98%
“…The contribution of AMF to P uptake reaches up to 77% under low P supply compared with only 49% under high P supply [85]. Furthermore, the commercial inoculum Mycobiol, consisting of Glomus spp., Entrophospora colombiana, and Acaulospora mellea, enhanced P acquisition and plant growth in a pot experiment [86]. González and Walter [87] observed that Glomus aggregatum increased P uptake and biomass production of inoculated plants compared.…”
Section: Effective Microbial Inoculationmentioning
confidence: 99%